Cutting through complexity: the Breathing, Thinking, Functioning clinical model is an educational tool that facilitates chronic breathlessness management - Anna Spathis (Nature Portfolio, 2021)
Abstract Chronic breathlessness is a distressing symptom that is challenging to manage. The Breathing, Thinking, Functioning clinical model is an educational tool developed to support breathlessness management. Health professionals report that the model increases clinician and patient understanding of this complex symptom, and provides a simple and structured approach to personalised self-management.